1999
DOI: 10.1089/jop.1999.15.257
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Effects of Antimuscarinic Compounds: Is Clinical Effect Determined by Binding Affinity for Muscarinic Receptors or Melanin Pigment?

Abstract: Although antimuscarinic drugs are being used with increasing frequency in clinical practice for the purposes of mydriasis and cycloplegia, the extent of their actions varies considerably between different compounds. Investigation of the binding characteristics of these agents revealed that as their reported clinical potency increased, so did their specific binding affinity for muscarinic receptors in the iris sphincter and ciliary muscle and their nonspecific binding affinity for melanin pigment. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
11
1
Order By: Relevance
“…It remains yet unknown as to why the side effects were more pronounced in our non-Asian cohort with high variation in iris color. Up to now, one can only speculate on the role of ocular melanin and the affinity of atropine for melanin [ 23 ]. This is in line with data from Nishiyama et al, who found no side effects 2 weeks after 0.01% atropine in Japanese children aged between 6 and 12 years [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It remains yet unknown as to why the side effects were more pronounced in our non-Asian cohort with high variation in iris color. Up to now, one can only speculate on the role of ocular melanin and the affinity of atropine for melanin [ 23 ]. This is in line with data from Nishiyama et al, who found no side effects 2 weeks after 0.01% atropine in Japanese children aged between 6 and 12 years [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non‐saturable binding, as well as internal redistribution of the drug affects the agonist – antagonist interactions and could explain the marked differences between individuals in ocular responses to anti‐muscarinic compounds. From a clinical standpoint, association of the compound with melanin may reduce the concentration of drug available to take effect at the muscarinic receptors (melanin acting as a ‘drug‐reservoir’; German et al ., 1999 ). Aravind Meon et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a study, it has been reported that all of the participants with presbyopia experienced marked improvement in near vision with the unique side effect of short-term dimming in vision due to decreasing of the amount of light which entered into the eye with pupil constriction. 23,24 Recently, it has been reported by Encore Vision/Novartis that EV06 ophthalmic solution including lipoic acid choline ester 1.5% improved binocular near acuity with no loss of the best-corrected distance vision. It is well known that the aging of crystalline lens diminishes the elasticity of the lens through the increasing protein sulfhydryl group oxidation to form protein cross-links, and the lens fibres harden and consequently, this causes accommodative amplitude loss and blurry near vision.…”
Section: • Reduce Inflammationmentioning
confidence: 99%
“…The big advantage is that if it does not work, patients can give up using the drop, as long as no long-term detrimental effects are discovered. 23,24,30 Review Presbyopia FOV Tears, a binocular presbyopia-correcting drop is a combination of parasympathetic, alpha agonists 1 and 2, an anti-cholinesterase and a NSAID. The drop affects the ciliary muscle, which causes a physiological accommodation and a dynamic pseudo-accommodation.…”
Section: • Reduce Inflammationmentioning
confidence: 99%